2011
DOI: 10.1161/circulationaha.111.048868
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Family History as a Risk Factor for Venous Thromboembolism

Abstract: V enous thromboembolism (VTE) is a multifactorial disease with many known genetic and acquired risk factors. 1 A positive family history is an independent risk factor for VTE that may reflect the presence of a hereditary thrombophilic disorder. However, the predictive value of a positive family history for detection of known heritable causes of VTE is low, 2,3 suggesting that there are as-yet undiscovered genetic or environmental risk factors that account for the familial clustering of this disorder. Article s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Smoking may represent a weak risk factor for DVT, especially in studies considering VTE events as the only outcome [19]; we found smoking to be relatively frequent in VTE (32.9%), but not enough to be independently associated with thrombotic risk. Family history is an independent risk factor for VTE, reflecting a hereditary thrombophilia [20]. However, our study indicated no association with VTE, which may be due to an underestimation of the frequency, since we considered only confirmed VTE of the siblings.…”
Section: Discussioncontrasting
confidence: 59%
“…Smoking may represent a weak risk factor for DVT, especially in studies considering VTE events as the only outcome [19]; we found smoking to be relatively frequent in VTE (32.9%), but not enough to be independently associated with thrombotic risk. Family history is an independent risk factor for VTE, reflecting a hereditary thrombophilia [20]. However, our study indicated no association with VTE, which may be due to an underestimation of the frequency, since we considered only confirmed VTE of the siblings.…”
Section: Discussioncontrasting
confidence: 59%
“…Although obesity appears to be a moderate risk factor for VTE [32,49], it can interact with other risk factors in VTE development and recurrence. Here, we have summarized the relationship of obesity with some common weak-to-moderate risk factors for VTE, including genetic factors, use of sex steroid hormones, inflammation, and insulin resistance [50,51].…”
Section: Interplay Of Obesity With the Risk Factors For Vtementioning
confidence: 99%
“…The annual incidence of VTE is one to two per 1,000 adults worldwide [1,3]. Several risk factors are associated with thrombosis, including older age, obesity, smoking, history of thrombosis, surgery, hospitalization, varicose veins, thrombophilia, oral contraceptives, and pregnancy [4][5][6][7]. Worldwide, PE, especially in postpartum and pregnant women, is the cause of maternal death [8].…”
Section: Introductionmentioning
confidence: 99%